Gender Disparities in Health-Related Behaviors: A Comprehensive Analysis of Smoking, Alcohol Consumption, Physical Activity, Nutrition, and Blood Pressure - Odeigah, Louis O.; Olalekan, Agede O.; Ogunjemilua, Sunday B.; Oyedepo, Dapo S.; Okoro, Peace N.; Sanni, Nasiru (Clinical and Research Journal in Internal Medicine, 2025)
Background: Gender disparities in health-related behaviors have significant implications for public health interventions. Aim: This comprehensive analysis aims to explore variations in smoking, alcohol consumption, physical activity, nutrition, and blood pressure between genders. Methods: In the Inter-University Consortium for Political and Social Research Study (ICPSR146521), data that had been gathered prospectively were used to assess the prevalence of metabolic syndrome, its risk factors, and the linked lifestyle in adult Myanmar inhabitants. Results: The study revealed noteworthy gender disparities in various health-related behaviors. Among passive smokers, no significant gender differences were observed. However, in active smokers, males exhibited notably higher rates than females. In the category of individuals who had never smoked, females predominated. For past smokers, females were more likely to have quit smoking successfully. Concerning alcohol consumption, males reported higher rates of past and current drinking, while females were more likely never to have consumed alcohol. Regarding physical activity, females were less likely to engage in exercise activities. Sedentary lifestyle patterns showed no significant gender differences. Conclusion: This analysis underscores the importance of recognizing gender-specific health-related behaviors and their implications. Understanding these differences is essential for tailoring effective public health strategies that address the unique needs and challenges faced by each gender. By acknowledging and addressing these disparities, healthcare providers and policymakers can develop more targeted interventions to promote healthy behaviors and reduce health inequalities. These findings provide a valuable foundation for further research and the development of gender-sensitive public health initiatives.